Biased Aggressive Attribution Among Department Heads - Wanas, Salam Thahir; Jouni, Ahmed Abdul-Kadhim (Journal of Posthumanism, 2025)
The interest of studies has increased in the process of realizing the reasons that led to aggressive behaviors among some towards others and understanding their intentions as hostile, especially in ambiguous situations, and that this bias in interpreting the intentions of others made individuals respond with an aggressive response in the social situations they face. In light of the above, the current research seeks to measure the biased aggressive attribution among department heads on the research sample of (300) department heads, male and female, who were chosen using a random stratified method and a proportional approach. In order to achieve the two research objectives, the researchers built a scale to measure the biased aggressive attribution according to Dodge’s theory (2006). In its final form, it consisted of (15) phrases. The researchers adopted the method of verbal situations, which somewhat represent the life situations of department heads, with two alternatives for answering in the form of answers for the biased aggressive attribution position. The department head chooses one of these answers, and when correcting, the answer that measures the biased aggressive attribution is given (2) degrees. As for If the department head chooses the second answer, which represents neutral attribution, he is given (1) point. After verifying their validity and reliability and analyzing their paragraphs statistically, the research results indicated that department heads do not have biased aggressive attribution, and there are no differences between department heads in biased aggressive attribution according to the gender variable (male, female) and specialization (scientific, humanities).